A framework for web-based dissemination of models and lessons learned from emergency-response exercises and operations. (1st January 2001) - Jenvald, Johan; Morin, Magnus; Kincaid, J. Peter
Emerging web-based technologies enable information sharing within and among rescue agencies and organisations. This development can facilitate education, training and development through effective distribution of documentation, models and lessons learned from training exercises and rescue operations. We discuss central aspects of this enterprise such as the need for domain-specific data models, methodologies for detailed exercise documentation, and the design of presentation and visualisation tools. Based on this investigation, we present a framework that supports modelling, documentation and visualisation of rescue operations for web-based distribution. We briefly describe the implementation of the components of the framework. Finally, we discuss how to apply the methodology and framework to training of first responders and university-level education of emergency managers and officials.